Notes to Philosophy 167: Class 9 -- Descartes' Principia: The Vortex Theory of the Heavens -- Part 11 - Part 12. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Descartes' Conception of the Problem -- How To Do Science: the Cartesian Solution.; Generally corresponds to the video segment: Class 9, Part 11 - 12.